2004
DOI: 10.1074/jbc.m403258200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent Induction of Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) and Fas/FasL Is Crucial for Efficient Influenza Virus Propagation

Abstract: Activation of the transcription factor NF-B is a hallmark of infections by viral pathogens including influenza viruses. Because gene expression of many proinflammatory and antiviral cytokines is controlled by this factor, the concept emerged that NF-B and its upstream regulator IB kinase are essential components of the innate antiviral immune response to infectious pathogens. In contrast to this common view we report here that NF-B activity promotes efficient influenza virus production. On a molecular level th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
236
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(252 citation statements)
references
References 63 publications
10
236
3
2
Order By: Relevance
“…Further investigation on the molecular mechanisms involved in FPRL1-mediated TRAIL expression showed that the TRAIL expression in THP-1 monocytes and neutrophils enhanced by W, F, and N36 peptides was dependent on NF-nB activation. These data are consistent with the reports that TRAIL expression was dramatically down-regulated by inhibition of NF-nB activity in Jurkat and primary T lymphocytes (35) and induced by influenza A virus infection in a NF-nB -dependent manner (36). Because the activation of NF-nB is usually involved in cell activation and Figure 4.…”
Section: Discussionsupporting
confidence: 82%
“…Further investigation on the molecular mechanisms involved in FPRL1-mediated TRAIL expression showed that the TRAIL expression in THP-1 monocytes and neutrophils enhanced by W, F, and N36 peptides was dependent on NF-nB activation. These data are consistent with the reports that TRAIL expression was dramatically down-regulated by inhibition of NF-nB activity in Jurkat and primary T lymphocytes (35) and induced by influenza A virus infection in a NF-nB -dependent manner (36). Because the activation of NF-nB is usually involved in cell activation and Figure 4.…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon may be explained by the homology between H5N1 NS1 protein and the cytoplasmic domain of the proapoptotic Fas antigen (15,17,19). Apoptosis can occur through the ligation of cell surface death receptors such as Fas/CD95, a member of the tumor necrosis factor receptor family (20,24,56). This event leads to the recruitment and activation of an adapter protein, FADD (Fas-associated death domain-containing protein), resulting in the activation of caspases that exist as inactive zymogens in normal cells (8,39).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inflammatory cytokines, which belong to the TNF superfamily and are responsible for inducing apoptosis, are known to be an important factor both in activating the immune system to exclude the virus and in the activation of virus replication (Ishikawa et al, 2005;Wurzer et al, 2004). To investigate whether Siva-1 functioned to effect the exclusion of influenza A virus or the acceleration of the virus replication, the virus replication in Siva-1-knockdown A549 cells was analysed by monitoring virus titre.…”
Section: Siva-1 Regulates the Replication Of Influenza A Virus Withoumentioning
confidence: 99%
“…Importantly, the stimulation of receptors by death ligands is also involved in the replication of influenza A virus. It has been reported that the expression levels of FasL and TRAIL are increased by infection with influenza A virus (Ishikawa et al, 2005), and the stimulation of the receptors by these ligands in virus-infected cells is required for the effective replication of influenza A virus (Wurzer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%